2015
DOI: 10.1007/s10800-015-0800-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of anode–cathode interaction in a polymer electrolyte fuel cell revealed by simultaneous current and potential distribution measurements under local reactant-starvation conditions

Abstract: Low stoichiometry operation of fuel cells induces nonuniformities in the current generation and electrode potentials across the active electrode area. In this study, current and potential distributions are measured simultaneously in a fuel cell operating under reactant (fuel/ air)-starvation conditions. During the galvanostatic operation under local reactant starvation, the localized increase of current density is observed closer to the inlet. Here under air starvation, cathode potentials dropped uniformly acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…They showed a degradation in the polarization curve and that the degradation was more significant at the inlet of the cell. Manokaran et al [27] observed the same effect. They ran a fuel cell in an oxidant and hydrogen starvation condition and measured the current density and potential at different spots on the reactant channel flow to determine the effect on performance.…”
Section: Effect On Performance and Agingmentioning
confidence: 63%
“…They showed a degradation in the polarization curve and that the degradation was more significant at the inlet of the cell. Manokaran et al [27] observed the same effect. They ran a fuel cell in an oxidant and hydrogen starvation condition and measured the current density and potential at different spots on the reactant channel flow to determine the effect on performance.…”
Section: Effect On Performance and Agingmentioning
confidence: 63%
“…The stoichiometry reduction generally causes a steeper inlet-to-outlet concentration gradient due to its higher depletion by the electrochemical reaction. This phenomenon typically occurs over a broad range of the oxygen stoichiometry [37,47,48]. For the fuel, similar effects tend to occur at stoichiometries very close to 1.0.…”
Section: Mild Fgsmentioning
confidence: 82%
“…On the other hand, the CDD profile in flow direction is known to be strongly dependent on the operation conditions [20,[38][39][40]. In particular, the relative humidity profile on the cathode (air) side has a major influence due to its high mass flow and therefore capacity to carry water [14,15].…”
Section: Operation Conditionsmentioning
confidence: 99%